An Insight into Anatomical Variations in Maxillary Molars: A Case Series - Nepal, Manisha; Gautam, Vanita; Shubham, Snigdha; Tripathi, Rupam; Sah, Rinku (Journal of Universal College of Medical Sciences, 2018)
The aim of this article is to show different anatomic complexities of the root canal system related to maxillary molars. Maxillary molars are presumed to have only three roots with three canals but this is not always the case, it might present with different variations. Some of the anatomical variations such as, mesiobuccal2 (MB2) canals in maxillary 1st and 2nd molars, two rooted maxillary 1st and 2nd molar, one rooted maxillary 2nd molar, C-shaped upper 2nd molar and maxillary 2nd molar with extra palatal root are reported in this case series. Hence, in treating each tooth every dentist must keep foresight that complex anatomy occurs often enough to be considered normal and manage them accordingly.